1978
DOI: 10.1111/j.1432-1033.1978.tb12725.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Tryptophan Residues of Lysozyme Using 1H Nuclear Magnetic Resonance

Abstract: The identification and complete assignment of the C-2 and N-1 proton nuclear magnetic resonances (NMR) of the six tryptophan residues of hen lysozyme are reported. Identification of the resonances required a detailed examination of the spectra of the protein in H20 and in 'HzO, and involved the application of spin-echo and Carr-Purcell-Meiboom-Gill pulse sequences. Assignment was achieved by observing the effects on the NMR spectra of performing specific chemical modifications, of binding paramagnetic species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

1981
1981
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 34 publications
3
23
1
Order By: Relevance
“…We demonstrated the error this can lead to in interpretation in a very early NMR study of a chemical modification of a tryptophan residue (Cassels et al 1978). We demonstrated the error this can lead to in interpretation in a very early NMR study of a chemical modification of a tryptophan residue (Cassels et al 1978).…”
Section: General Comments On Structural Definition By Nmr and X-ray Dmentioning
confidence: 87%
See 1 more Smart Citation
“…We demonstrated the error this can lead to in interpretation in a very early NMR study of a chemical modification of a tryptophan residue (Cassels et al 1978). We demonstrated the error this can lead to in interpretation in a very early NMR study of a chemical modification of a tryptophan residue (Cassels et al 1978).…”
Section: General Comments On Structural Definition By Nmr and X-ray Dmentioning
confidence: 87%
“…Relaxation of aromatics, fast flipping rates, > 105 s-1 is very common (Wtithrich 1986) as is oscillating behaviour of tryptophan (Cassels et al 1978). Life is a product of the existence of water.…”
Section: Protein Surfacesmentioning
confidence: 99%
“…By nuclear magnetic resonance studies (NMR) (Cassels et al 1978;Lenkinsky et al 1979) and optically detected magnetic resonance (ODMR) (Rousslang et al 1979) it has been possible to determine the degree of availability towards the solvent of Trp residues in lysozyme. In this way it has been shown that residue 62 is the most exposed one, followed by residues 123 and 63; the others are quite more shielded.…”
Section: T/t 0 = Fle-klt+f2 E-k2tmentioning
confidence: 99%
“…Photo-CIDNP (chemically induced nuclear polarisation) is an interesting technique for the study of surface positioned aromatic residues in proteins (Broadhurst et al, 1991;Cassels et al, 1978;Hore and Kaptain, 1983;Scheffier et al, 1985). By introducing a dye and exciting it with a laser, it is possible to transfer magnetisation to aromatic residues, where it can be observed.…”
Section: Other Applications Of Nmrmentioning
confidence: 99%